Impact of absolute values and changes in meteorological and air quality conditions on community-acquired pneumonia in Germany - Khan, Saeed Akhtar; Brenner, Thomas; Link, Ann-Christine; Reudenbach, Christoph; Bendix, Jörg; Weckler, Barbara; Kutzinski, Max; Rupp, Jan; Witzenrath, Martin; Rohde, Gernot Gerhard Ulrich; Pletz, Mathias; Bertrams, Wilhelm; et al. (International journal of biometeorology, 2025)
Community-acquired pneumonia (CAP) is a major global health concern as it is a leading cause of morbidity, mortality and economic burden to the health care systems. In Germany, more than 15,000 people die every year from CAP. Climate change is altering weather patterns, and it may influence the probability and severity of CAP. The increasing f!082447861!requency and intensity of extreme weather events necessitate the study of their impact on CAP hospitalizations. In this regard, we examine the influence of absolute values and changes in various meteorological and air quality conditions on the frequency of CAP hospitalizations. We matched weather data to the German CAPNETZ-Cohort of 10,660 CAP patients from 22 healthcare facilities between 2003 and 2017. Our findings show that daily fluctuations in meteorological conditions (maximum temperature, 99th percentile precipitation), apart from relative humidity, are likely to result in triggering CAP hospitalizations than absolute conditions. In contrast, the absolute values of air quality (CO, NO2, O3, PM2.5, SO2, and total aerosols) are found to exert a greater influence on CAP hospitalizations than changes in air quality. The study outcomes have implications for public health measures, early warning systems, and public awareness, with the aim of mitigating the risk of CAP.
Gesehen am 26.01.2026
Online veröffentlicht: 24. Dezember 2024